PENGARUH SIFAT QANA’AH TERHADAP PERILAKU KONSUMTIF PADA SISWA/ (I) SMA NEGERI 3 BANDA ACEH - Ika Rahmadani; Rahmat Rizki; Winda Putri Diah Restya (universitas teuku umar, 2018)
AbstractThis study aims to determine the effect of Qana'ah trat on consumptive behavior. The population of this research is high school students in SMA Negeri 3 Banda Aceh. The research sample amounted to 238 students. The sampling method is a cluster sampling, which is the selection of samples selected by group. The measuring instrument in this study uses the consumptive behavior scale and the Qana'ah trait scale. Data analysis used is simple linear regression analysis. The results of data analysis showed that there was a significant influence between qana'ah trait on consumptive behavior with the value (R Square) 0.218 and sig 0.000 value, meaning that the trait of qana'ah influences on consumptive behavior by 21.8%. The higher the qana'ah nature, the lower the consumptive behavior. The weaknesses in this study include, first, the item number of the both of scale are too much so that there are some subjects complaining of experiencing saturation in filling out the questionnaire. Second, the response of some subjects on this scale is not in accordance with the actual conditions, so that some subjects do not want to acknowledge what is inside them and tend to want to look good when filling the scale.Keywords: Qana'ah Trait, Consumptive Behavior